Baltic Salmon and Trout Assessment Working Group (WGBAST) - Bajinskis, Janis; Bernaś, Rafal; Dahlgren, Elin; Dannewitz, Johan; Debowski, Piotr; Ek, Caroline; Ivanauskas, Edgaras; Kagervall, Anders; Karlsson, Konrad; Kesler, Martin; Kontautas, Antanas; Leinonen, Tuomas; et al.
2024